HIDROPONIK SEBAGAI PEMANFAATAN LAHAN KOSONG DALAM PEMENUHAN KEBUTUHAN PANGAN MANDIRI - Oktavia, Novi Tri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The purpose of this community service is to educate students about the benefits of hydroponics in providing healthy food, increasing food security, and reducing the environmental impact of conventional agriculture. The method of this community service activity is carried out with an approach. This community service activity was attended by 104 4th semester students of Tadris Social Sciences of UIN Sayyid Ali Rahmatullah Tulungagung consisting of 33 from class A, 34 from class B, and 37 from class C. The results of this community service show that the students are more interested in hydroponics than in conventional agriculture. The results of this community service show that Tadris Social Science students are very enthusiastic about participating in hydroponic plant cultivation activities and are interested in practicing hydroponic plant cultivation in their yard.